Safeguarding Sovereignty: Indonesia's Solution to the Raw Materials Case in WTO - Zaki, Muhammad Reza Syariffudin; Armanto, Muhammad Haykal; Albar, Rafsi Azzam Hibatullah; Koos, Stefan (UI Scholars Hub, 2023)
Indonesia’s export restriction on raw materials was based upon Law No. 4 of 2009 on Mineral and Coal Mining as amended with Law No. 3 of 2020. January 1st of 2020 marks nickel to be the first mineral to be affected by the raw mineral export ban policy. This measure has sparked a controversy in the international community, as the European Union deemed that this measure is against the principles of the World Trade Organization of nonrestrictive trade policies. This phenomenon was brought to the Dispute Settlement Body of the WTO as DS592 – Indonesia Measures Relating to Raw Materials. Although the Indonesian government has lost the case against the European Union, the Indonesian government is adamant on proceeding with this measure to further develop the downstream industry of raw minerals in Indonesia. Since then, Indonesia has filed the appeal for the panel report of the DS592 case and shows no sign of stopping the nationwide export ban on raw minerals, with bauxite, copper, and tin on the horizon. Therefore, the invocation of Article XXI GATT could be used as a strategy to avoid scrutiny from the international community, by invoking a national security exception to implement measures inconsistent to the principles of the WTO. Thus, the Indonesian government is able to protect and secure their nation’s fundamental principal as a sovereign nation with control over its raw materials.